2017
DOI: 10.5535/arm.2017.41.5.851
|View full text |Cite
|
Sign up to set email alerts
|

The Validity of the Bayley-III and DDST-II in Preterm Infants With Neurodevelopmental Impairment: A Pilot Study

Abstract: ObjectiveTo identify the usefulness of both the Bayley Scales of Infant and Toddler Development, 3rd edition (Bayley-III) and Denver Developmental Screening Test II (DDST-II) in preterm babies with neurodevelopmental impairment, considering the detection rate as regulation of criteria.MethodsRetrospective medical chart reviews which included the Bayley-III and DDST-II, were conducted for 69 preterm babies. Detection rate of neurodevelopmental impairment in preterm babies were investigated by modulating scaled … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
9
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 12 publications
(9 citation statements)
references
References 16 publications
0
9
0
Order By: Relevance
“…The 1992 revision of the DDST, the DDST-II, has been validated across many populations of children with developmental disabilities and brain injuries. 12 We selected specific items from the DDST-II to represent the range of skills observed in the Aicardi Goutières syndrome population.…”
Section: Discussionmentioning
confidence: 99%
“…The 1992 revision of the DDST, the DDST-II, has been validated across many populations of children with developmental disabilities and brain injuries. 12 We selected specific items from the DDST-II to represent the range of skills observed in the Aicardi Goutières syndrome population.…”
Section: Discussionmentioning
confidence: 99%
“…The DDST-II and K-ASQ may present some difficulties in reflecting special developments in Korean children. Recently studies reported that the detection rate of neurological impairment for the DDST-II was 50.7% in neurological impairment of Korean infants [31], and K-ASQ showed low validity for screening neurodevelopmentally delayed premature infants [9]. To reinforce this point, the K-DST was developed with cultural appropriateness in mind by the Korean Society of Pediatrics in 2014 [12].…”
Section: Discussionmentioning
confidence: 99%
“…However, the usefulness of the K-DST to evaluate developmental delay in preterm children has not been studied. Having a useful developmental screening test for preterm infants is very important for the early diagnosis of developmental delays, as some cases could resolve to almost normal developmental outcomes when early intervention and rehabilitation programs are used [11,31].…”
Section: Discussionmentioning
confidence: 99%
“…It is an appropriate screening tool with excellent reliability and validity as well as clinical significance 4,14,15) . The BSID-III can evaluate cognition, language, and motor domains as separate CS, as well as assess developmental level, by subdividing the sections into "receptive language, " "expressive language, " and "fine and gross motor" using SS 3) . Therefore, it avoids problems associated with the lack of standardized scores for cognitive vs. language skills and gross vs. fine motor skills 16) .…”
Section: Discussionmentioning
confidence: 99%
“…For example, a low MDI score could reflect a delay in language or cognitive development, or both. The third edition of the Bayley scales, which was published in 2006 for infants and children aged 1 to 42 months, attempted to overcome these limitations by subdividing the composite scores (CS) of the cognitive, language, and motor domains 2,3) . Thus, scaled scores (SS) can assess receptive/expressive communication and fine/gross motor development.…”
Section: Introductionmentioning
confidence: 99%